2015
DOI: 10.1007/jhep03(2015)150
|View full text |Cite
|
Sign up to set email alerts
|

From U(1) to E8: soft theorems in supergravity amplitudes

Abstract: It is known that for N = 8 supergravity, the double-soft-scalar limit of a n-point amplitude is given by a sum of local SU(8) rotations acting on a (n−2)-point amplitude. For N < 8 supergravity theories, complication arises due to the presence of a U(1) in the U(N ) isotropy group, which introduces a soft-graviton singularity that obscures the action of the duality symmetry. In this paper, we introduce an anti-symmetrised extraction procedure that exposes the full duality group. We illustrate this procedure fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…We find that the double soft behavior is governed by R-symmetry generators acting on a lower-point amplitude, resembling the results of supergravity theories found in [54,56,57], although the vacuum structure of SYM is quite different from that of supergravity theories. Finally, we consider double-soft scalars in the open superstring theory.…”
Section: Jhep07(2015)095supporting
confidence: 58%
See 3 more Smart Citations
“…We find that the double soft behavior is governed by R-symmetry generators acting on a lower-point amplitude, resembling the results of supergravity theories found in [54,56,57], although the vacuum structure of SYM is quite different from that of supergravity theories. Finally, we consider double-soft scalars in the open superstring theory.…”
Section: Jhep07(2015)095supporting
confidence: 58%
“…For example, Arkani-Hamed et al [54] have shown that the double soft limit of scalars in N = 8 supergravity exhibit the expected E 7(7) symmetry of the scalar moduli space, in a manner analogous to the classic soft-pion theorem of [52,55]. This result was recently extended to the four-dimensional supergravity theories with N < 8 supersymmetry, and the N = 16 supergravity in three dimensions in [56]. Furthermore, supergravity amplitudes in both four and three dimensions with two soft fermions were studied in [57], and new soft theorems were proposed.…”
Section: Jhep07(2015)095mentioning
confidence: 71%
See 2 more Smart Citations
“…(2.8), stems from the original three-point vertices in the supergravity action as well as those that arise from the anomalous effective action. For the former, the contribution is zero since it can be derived from the tree-level soft theorems [32], which must vanish due to the scalar's role as parameterising the degenerate vacua. For the later, the corresponding three point vertex is R 2 φ and R 2φ , which would generate a term that is of order q 2 in the numerator, and thus, in the q → 0 limit, suppresses the 1/p i · q propagator leading to a vanish result.…”
Section: Soft Behaviour With Anomalous U(1) Symmetrymentioning
confidence: 99%